INTENSITAS SERANGAN PENGGEREK KAYU DI LAUT PADA KAYU MERANTI DAN BENGKIRAI - Hikma Yanti; Muhammad Dirhamsyah; Ahmad Yani; Yeni Mariani; Fathul Yusro (Jurnal Penelitian Hasil Hutan, 2026)
The use of transportation such as wooden ships, docks, piles, and buildings at sea is mostly made of wood. The wood used is prone to attack by marine borers, which are wood-eating pests found in marine environments. The purpose of this study was to determine  the effect of differences in water depth on the intensity of marine wood borer attacks, and to identify the types of wood borers that attack meranti and bengkirai wood at the Mempawah River estuary. This study was conducted for 3 months at the Mempawah River Estuary, Mempawah Regency, West Kalimantan Province, Indonesia. The test used Meranti and Bengkirai wood test samples measuring 2 cm x 5 cm x 30 cm. Data analysis used a Completely Randomized Design (CRD) with 5 replications, so that there were 15 test samples of each type of wood. The results showed that the natural durability of wood (percentage of intensity of attacks) on meranti and bengkirai wood was included in class I durability (very resistant) to attacks by wood borers at sea. Intensity of attacks on meranti wood from the lowest to the highest in sequence was a depth of 5 cm (3.88%), 25 cm (7.37%), and 50 cm (12.23%). Intensity of attacks on bengkirai wood from the lowest to the highest in sequence was a depth of 5 cm (2.73%), 25 cm (3.54%), and 50 cm (9.09%). This difference in depth has a very significant effect on the intensity of attacks value of the test sample. The types of marine wood borers found in the waters of the Mempawah River estuary are Limnorium sp., Balanus sp., Nereis sp., and Teredo sp.